Development of Web-Based Mathematics Learning Media to Improve Reasoning Ability and Self-Efficacy of High School Students - Wahyuni, Sri; Dewi, Izwita; Nasution, Hamidah (Jurnal Perspektif, 2025)
The purpose of this study was to determine the validity, practicality and effectiveness of web-based mathematics learning media to improve students' reasoning skills and self-efficacy, 1 and improve students' reasoning skills and self-efficacy. This type of research is Thiagarajan's development research, namely the 4-D model. The subjects in this study were 30 students of MAN 1 Medan Class X-18. Research results; The web-based mathematics learning media developed has met the valid and practical criteria in terms of material, appearance, interactivity, and ease of use. This eligibility was obtained based on the results of validation by material experts, media experts, as well as the results of limited trials and extensive trials conducted on students. This learning media has proven effective in improving students' mathematical reasoning skills. This is due to a significant increase in mathematical reasoning ability scores after students used the developed learning media compared to before using the media. The use of web-based mathematics learning media also makes a positive contribution to improving students' reasoning and self-efficacy. Student participants showed increased confidence in their ability to understand and solve mathematical problems.